Fabrication of hydrangea-shaped Bi2WO6/ZIF-8 visible-light responsive photocatalysts for degradation of methylene blue. (November 2022) - Zhang, Xinling; Yuan, Ning; Chen, Tianxiang; Li, Bowen; Wang, Qibao
Abstract: In this paper, the hydrangea-shaped Bi2 WO6 /ZIF-8 (BWOZ) visible light photocatalysts have been prepared via a facile synthetic strategy for the first time. The constructed BWOZ composites were systematically studied by a series of characterization techniques. The SEM results manifested the octahedral ZIF-8 coated the flower-like Bi2 WO6 uniformly and the composition of BWOZ composites had been confirmed by XPS measurement. And the photocatalytic activity was evaluated by eliminating methylene blue with the help of visible light. The results showed that 7%-BWOZ (7.0 wt% Bi2 WO6 ) exhibited better photodegradation capability than pure Bi2 WO6 and ZIF-8. Compared with Bi2 WO6, the photocatalytic degradation of methylene blue by 7%-BWOZ could reach 85.7%. In addition, the pseudo-first-order kinetic constant of 7%-BWOZ was 23.00 and 1.61 times that of pristine Bi2 WO6 and ZIF-8, respectively. The improved photocatalytic ability of BWOZ systems may be due to the construction of heterojunctions between Bi2 WO6 and ZIF-8, which resulted in the rapid separation of photogenerated carriers. Additionally, the specific surface area of the formed BWOZ system was also improved in comparison with the flower-shaped Bi2 WO6, and thus more active sites could be provided to contact with methylene blue molecules, thereby achieving better removal capacity. Moreover, trapping experiments and electron spin resonance results further illustrated that the coexistence of multiple free radicals realized efficient degradation of methylene blue. More importantly, the photocatalytic property of the 7%-BWOZ composite remained even after three cycles. Furthermore, a feasible photodegradation mechanism was also explored in depth. Graphical abstract: Image 1 Highlights: A novel photocatalyst of Bi2 WO6 /ZIF-8 was fabricated via a facile synthetic strategy. The Bi2 WO6 /ZIF-8 can photodegrade methylene blue (MB) from wastewater efficiently. The Bi2 WO6 /ZIF-8 can be applied in actual wastewater and possessed high renewability. A convincible photocatalytic mechanism for removing MB by Bi2 WO6 /ZIF-8 was provided.